Faktor-Faktor yang Berhubungan dengan Kejadian Luka Dekubitus Akibat Penggunaan Alat Medis di Ruang PICU (Politeknik Kesehatan Kemenkes Mamuju, 2020)
The use of medical devices in patients treated at the Pediatric Intensive Care Unit (PICU) is very high. Patients who are treated in intensive care are also at risk for medical device-related pressure injury (MDRPI). This study aimed to determine the factors associated with the incidence of MRDPI in the Pediatric Intensive Care Unit (PICU) RSUP DR. Wahidin Sudirohusodo Makassar. This study used an observational analytic method with a prospective cohort approach. The Sampling method used a simple random sampling of 76 people. This research was conducted on 8 May - 6 July 2019. The data collection technique used an observation sheet with the research instrument used in the form of the Pediatric Early Warning Scoring System to assess critical conditions, the level of awareness was fully used Full Outline of UnResponsiveness score (FOUR Score). The data were analyzed tested by using the statistical the Chi Square with a confidence level of 95%. All data were analyzed using the SPSS version 21.0 program (SPSS, Inc. Chicago, IL). Factors associated with the MDRPI incidence include critical conditions based on PEWSS (p = 0.002), level of awareness based on the FOUR Score (p = 0.025), number of devices installed (p = 0.015), and fixation techniques (p = 0.025). As for peripheral tissue perfusion (p = 0.268), albumin (p = 0.309), skin moisture (p = 0.888) were not related. Factors associated with the incidence of MDRPI include critical condition, level of awareness, number of devices installed, and fixation techniques. It’s recommended to make preventive efforts.